2014
DOI: 10.1177/107327481402100107
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Demographics and Overall Survival of Non–Small-Cell Lung Cancer Patients at Moffitt Cancer Center from 1986 to 2008

Abstract: Background An assessment of historical trends in patient survival is important to determine the progress towards patient outcomes and to reveal where advancements must be made. The goal of this study was to assess changes in demographics and overall survival of non-small cell lung cancer (NSCLC) patients who were seen at the H. Lee Moffitt Cancer Center (MCC) and Research Institute spanning over 22 years. Methods This analysis included 4,997 NSCLC patients who were treated at the MCC over five time periods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Specifically, the 2-year survival for patients with ES-SCLC was 1.5% in 1973 and improved to 4.6% by 2000 and the 5-year survival rate for patients with LS-disease increased from 4.9% in 1973 to 10% in 1998. In a previous study 20 we found significant differences in demographic characteristics of non-small cell lung cancer patients from the same time span of this analysis (1986 to 2008). Specifically, the percentage of patients who were diagnosed over the age of 70 years increased from 19.8% to 38.4%, the percentage of women increased from 35.7% to 50.9%, and the percentage of current smokers decreased from 47.8% to 28.3%.…”
Section: Discussionmentioning
confidence: 56%
“…Specifically, the 2-year survival for patients with ES-SCLC was 1.5% in 1973 and improved to 4.6% by 2000 and the 5-year survival rate for patients with LS-disease increased from 4.9% in 1973 to 10% in 1998. In a previous study 20 we found significant differences in demographic characteristics of non-small cell lung cancer patients from the same time span of this analysis (1986 to 2008). Specifically, the percentage of patients who were diagnosed over the age of 70 years increased from 19.8% to 38.4%, the percentage of women increased from 35.7% to 50.9%, and the percentage of current smokers decreased from 47.8% to 28.3%.…”
Section: Discussionmentioning
confidence: 56%
“…2 In the United States, the five-year relative survival rate for all lung cancers is 17% (i.e., non-small cell lung cancer [NSCLC] and small cell lung cancer combined [SCLC]) 4 .Among NSCLCs, the five-year relative survival rate is 21% for all stages combined 4 and SCLCs have an overall 5-year survival rate of approximately 6% 5 . The overall prognosis for NSCLC remains poor and prognostic factors associated with poor survival include late stage diagnosis, current smoking status, advanced age, male sex, poor pulmonary function, presence of cardiovascular disease, non-squamous cell histology, and pneumonectomy 6–10 .Among SCLC patients, poor prognosis is associated with age greater than 70 year, male sex, relapsed disease, extensive-stage disease, weight loss greater than 10% of body weight at diagnosis, and poor performance status 1115 .Despite the poor patient outcomes associated with a lung cancer diagnosis, the emergence of immunotherapy/immune checkpoint inhibitors have demonstrated durable long-term survival in some patients 16,17 . As such, these therapies may hold the key in improving lung cancer survival and possibly making lung cancer curable in the early-stage setting and/or a chronic disease for patients with metastatic disease 18 .…”
Section: Burden Of Lung Cancer Globally and In The United Statesmentioning
confidence: 99%
“…Among patients with NSCLC, 10-25% present with CNS metastases at the time of diagnosis and up to 50% will develop CNS metastases at some point during the course of their disease (2,3). The incidence of CNS metastases seems to have further increased over the last years (4), possibly due to a more widespread use of magnetic resonance imaging (MRI) leading to early diagnosis (5), and to the improved efficacy of systemic therapies in controlling extracranial disease and prolonging survival, therefore allowing CNS micro-metastases to grow and become clinically evident (6). Unfortunately, the development of CNS metastases has a negative impact on quality of life, resource utilization and survival of patients with NSCLC (7).…”
Section: Introductionmentioning
confidence: 99%